Predicting Public Interest in Nonsurgical Cosmetic Procedures Using Google Trends. (2nd October 2019) - Tijerina, Jonathan D; Morrison, Shane D; Nolan, Ian T; Parham, Matthew J; Nazerali, Rahim
Abstract: Background: Google Trends (GT) provides cost-free, customizable analyses of search traffic for specified terms entered into Google's search engine. GT may inform plastic surgery marketing decisions and resource allocation. Objectives: The aim of this study was to determine GT's utility in tracking and predicting public interest in nonsurgical cosmetic procedures and to examine trends over time of public interest in nonsurgical procedures. Methods: GT search volume for terms in 6 ASPS and ASAPS nonsurgical procedure categories (Botox injections, chemical peel, laser hair removal, laser skin resurfacing, microdermabrasion and soft tissue fillers [subcategories: collagen, fat, and hyaluronic acid]) were compared with ASPS and ASAPS case volumes for available dates between January 2004 and March 2019 with the use of univariate linear regression, taking P < 0.01 as the cutoff for significance. Results: Total search volume varied by search term within the United States and internationally. Significant positive correlations were demonstrated for 17 GT terms in all 6 ASPS and ASAPS categories: "Botox®, " "collagen injections, " "collagen lip injections" with both databases; and "chemical skin peel, " "skin peel, " "acne scar treatment, " "CO2 laser treatment, " "dermabrasion, " "collagen injections, " "collagen lip injections, " "fat transfer, " "hyaluronic acid fillers, " "hyaluronic acid injection, " "hyaluronic acid injections, " "Juvederm®, " and "fat transfer" with just 1 database. Many search terms were not significant, emphasizing the need for careful selection of search terms. Conclusions: Our analysis further elaborates on recent characterization of GT as a powerful and intuitive data set for plastic surgeons, with the potential to accurately gauge global and national interest in topics and procedures related to nonsurgical cosmetic procedures.